2022
DOI: 10.1016/j.ajoc.2022.101356
|View full text |Cite
|
Sign up to set email alerts
|

In office management of optic capture of scleral fixated posterior chamber intraocular lenses

Abstract: Introduction Optic capture of sutured scleral fixated posterior chamber intraocular lenses (PC IOLs) is an occasional complication resulting in blurred vision and discomfort. Methods A retrospective study of the management of 18 eyes (3.6%) with optic capture out of 495 eyes with scleral fixated IOLs during the study period. 54 procedures were performed in the management of optic capture of sutured scleral fixated PC IOLs. An in-office technique was utilized to relieve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…This xed position close to the iris may increase the risk of iris-optic capture and subsequent complications. In this study, iris-optic capture was found in approximately 17% of patients (4 of 24 eyes) who only underwent sutured SF IOL surgery, which could lead to visual impairments such as intraocular hemorrhage and CME [9].…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This xed position close to the iris may increase the risk of iris-optic capture and subsequent complications. In this study, iris-optic capture was found in approximately 17% of patients (4 of 24 eyes) who only underwent sutured SF IOL surgery, which could lead to visual impairments such as intraocular hemorrhage and CME [9].…”
Section: Discussionmentioning
confidence: 70%
“…1). This complication can result in problems such as pain, high intraocular pressure, uveitis, pupillary block glaucoma, iris cha ng, pigment dispersion glaucoma, cystoid macular edema (CME), hyphema, or vitreous hemorrhage [9].…”
Section: Introductionmentioning
confidence: 99%
“…Kokame et al ( 8 ) suggested that in-office management was a good option for managing optic capture. Although this procedure can be performed in the office without discomfort or significant complications, pupillary optic capture may recur after the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Most cases of optic capture have been managed in the office by pushing the optic posterior to the iris using a 30-guage needle (8). However, repeated recurrence of pupillary optic capture despite these techniques may warrant surgical interventions, including IOL repositioning (9)(10)(11) and exchange (10).…”
Section: Introductionmentioning
confidence: 99%
“…Because the importance of postoperative miotic agent use in optic capture has been reported in many studies. 6 Also, was a myotic agent injected into the anterior chamber during correction? I congratulate the authors once again for this beautiful work.…”
mentioning
confidence: 99%